the effects of suggested training units upon physical and movements of mini hand ball sport - Nourddine nessil; dilmi mohamed; قيال مورد (sports creativity, 2025)
This study consider mini handball ,the research was brief under the title: the effects of suggested training units upon physical and movements of mini hand ball sport. The study was conducted on sports star club of El Geudid ,where the main objective of this study was to know the effects of training units on developing movements skills and physical abbilities (speed , strength, flexibility, and manouvers) and the expirimental method was done through this study on two groups of 16 players .the research concluded to the existance of an effects on physical abilities but less effect on movements abilities .the researchers recommended a guided sessions of training based on chronological order of training load